Association between transient receptor potential melastatin genotypes and the prostate surface antigen levels in BPH patients - Ongonga, Royronald Ochieng; Menza, Nelson; Demba, Rodgers Norman (International Journal of Research in Medical Sciences, 2024)
Background: Benign Prostate Hyperplasia (BPH) is a prevalent condition among older males, characterized by an enlarged prostate gland leading to lower urinary tract symptoms and impacting quality of life. Transient receptor potential melastatin (TRPM) genes regulate various physiological processes. Methods: We studied 194 BPH patients and 194 healthy controls, genotyping six selected TRPM gene SNPs. PSA levels were measured using the Cobas® e411 analyzer. Results: Prostate-specific antigen (PSA) levels were significantly higher in BPH patients (135.76±578.03 ng/mL) than in controls (2.01±1.09 ng/mL). TRPM2 (rs168355) and TRPM7 (rs2362295) genotypes were significantly associated with elevated PSA levels. The TRPM2 GG genotype was associated with decrease in the likelihood of severe PSA levels (OR=0.34, 95% CI: 0.12-0.96, P=0.034), while the TRPM7 CC genotype showed increased odds for severe PSA levels (OR=1.48, 95% CI: 1.08-3.56, P=0.041). Conclusions: Our findings suggest a potential link between TRPM gene variants and the severity of prostatic changes reflected in PSA secretions, indicating the need for further research to understand the underlying mechanisms and clinical implications.